Controlling attention to nociceptive stimuli with working memory. - Valéry Legrain; Geert Crombez; André Mouraux (PLoS ONE, 2011)
BACKGROUND: Because pain often signals the occurrence of potential tissue damage, a nociceptive stimulus has the capacity to involuntarily capture attention and take priority over other sensory inputs. Whether distraction by nociception actually occurs may depend upon the cognitive characteristics of the ongoing activities. The present study tested the role of working memory in controlling the attentional capture by nociception. METHODOLOGY AND PRINCIPAL FINDINGS: Participants performed visual discrimination and matching tasks in which visual targets were shortly preceded by a tactile distracter. The two tasks were chosen because of the different effects the involvement of working memory produces on performance, in order to dissociate the specific role of working memory in the control of attention from the effect of general resource demands. Occasionally (i.e. 17% of the trials), tactile distracters were replaced by a novel nociceptive stimulus in order to distract participants from the visual tasks. Indeed, in the control conditions (no working memory), reaction times to visual targets were increased when the target was preceded by a novel nociceptive distracter as compared to the target preceded by a frequent tactile distracter, suggesting attentional capture by the novel nociceptive stimulus. However, when the task required an active rehearsal of the visual target in working memory, the novel nociceptive stimulus no longer induced a lengthening of reaction times to visual targets, indicating a reduction of the distraction produced by the novel nociceptive stimulus. This effect was independent of the overall task demands. CONCLUSION AND SIGNIFICANCE: Loading working memory with pain-unrelated information may reduce the ability of nociceptive input to involuntarily capture attention, and shields cognitive processing from nociceptive distraction. An efficient control of attention over pain is best guaranteed by the ability to maintain active goal priorities during achievement of cognitive activities and to keep pain-related information out of task settings.